CAN GENRE-SPECIFIC DIY CORPORA, COMPILED BY LEGAL TRANSLATORS THEMSELVES, ASSIST THEM IN ‘LEARNING THE LINGO’ OF LEGAL SUBGENRES? - SCOTT, Juliette (Comparative Legilinguistics, 2012)
This paper presents a study aimed at examining whether DIY corpora compiled by professional legal translators can assist them in their role as learners of legal sublanguages, particularly those translators working into non-native target languages. A procedural DIY corpus methodology has been developed, involving the framed retrieval of authoritative legal texts from Internet repositories or other sources by legal translators themselves, according to their specific needs or those of particular projects, bearing in mind at all times feasibility in the workplace. Target audience expectations and requirements are also an important consideration in the project. A pilot study performing some initial testing with professional legal translators in certain legal genres and different languages has been completed and will be reported on. Results so far seem to indicate that compilation of such corpora can be achieved in an average of 30-45 minutes, in line with users' expressed criteria. It is posited that these highly specialised corpora may provide translators with some additional reference material that they are sorely lacking due to the absence or shortage in many language combinations of legal dictionaries or thesauri, in particular as regards collocations. It is hoped that a contribution may be made to professional practice in the long term.